Build The Ecclesiology-Theology Contextual In GKPA - Ramli Harahap (the International Journal of Education, Theology, and Humanities, 2021)
This research focuses on the ecclesiology of the Christian Protestant Angkola Church (GKPA). GKPA has implemented its ecclesiology for a long time. For a few decades GKPA's ecclesiology was dominated by the thinking and understanding of European ecclesiological heritage through zending (missionary) institutions that had worked and served in the Angkola-Mandailing area. The approach taken in this research is a grounded theory approach. This approach was chosen because of a lack of comprehensive knowledge regarding specific factors and inter-factor relationships that include the evolutionary ecclesiology process of GKPA, Patanakhon Hata ni Debata tu Luat Angkola (Sowing the Word of God to the Angkola region) at the beginning towards new ecclesiology GKPA Excellent Ministry in Togetherness. The process of evolution of the GKPA ecclesiology shows the new perspective of the GKPA’s ecclesiology theory and/or to find a new and relevant contextual ecclesiology’s theory of GKPA. The novelty of this article is to offer a new theory in ecclesiology namely: Excellent Ministry Ecclesiology in Togetherness. This ecclesiology is a new offer for GKPA to achieve GKPA's vision and mission to be "a Church that has Excellent Ministry in Togetherness".